PENGARUH SISTEM PENGENDALIAN INTERNAL, AKUNTABILITAS, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP IMPLEMENTASI GOOD CORPORATE GOVERNANCE - Sabrina, Nina; Kusumawaty, Mia; Buana, Adelia Satiara; Welly, Welly; Djuniar, Lis (Universitas Muhammadiyah Palembang, 2024)
This study aims to investigate the influence of internal control systems, accountability, and human resource competence on the implementation of good corporate governance in State-Owned Manufacturing Companies in Palembang City. The research method employed is associative research involving 50 respondents comprising Internal Auditors, Financial Managers, HR Managers, Accounting Department, and HR Department employees from 4 manufacturing companies. Data collection was conducted through questionnaire distribution using purposive sampling method. Quantitative analysis was employed as the analytical method. The results indicate that simultaneously, internal control systems, accountability, and human resource competence significantly influence the implementation of good corporate governance. Partially, internal control systems, accountability, and human resource competence variables also significantly affect the implementation of good corporate governance.